2011
DOI: 10.1371/journal.pone.0022748
|View full text |Cite|
|
Sign up to set email alerts
|

Time-Course of Changes in Inflammatory Response after Whole-Body Cryotherapy Multi Exposures following Severe Exercise

Abstract: The objectives of the present investigation was to analyze the effect of two different recovery modalities on classical markers of exercise-induced muscle damage (EIMD) and inflammation obtained after a simulated trail running race. Endurance trained males (n = 11) completed two experimental trials separated by 1 month in a randomized crossover design; one trial involved passive recovery (PAS), the other a specific whole body cryotherapy (WBC) for 96 h post-exercise (repeated each day). For each trial, subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
145
3
13

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(171 citation statements)
references
References 59 publications
10
145
3
13
Order By: Relevance
“…In contrast other research on plyometric exercise suggested that CRP increased only 2 days after training 22 . In other hands CRP production in our investigation is lower than plyometric and severe exercise 12,26 that it is same with the study on resistance or aerobic exercise 27 .…”
Section: Discussionsupporting
confidence: 90%
“…In contrast other research on plyometric exercise suggested that CRP increased only 2 days after training 22 . In other hands CRP production in our investigation is lower than plyometric and severe exercise 12,26 that it is same with the study on resistance or aerobic exercise 27 .…”
Section: Discussionsupporting
confidence: 90%
“…Based on obtained results, the authors suggest that although cryostimulation does not increase the risk of proprioceptive related injury, it is ineffective in improving recovery if administered 24h after exercise. In another study [Pournot et al 2011] researchers compared the effect of two different recovery modalities: cryostimulation (3 min at -110°C) and passive recovery, on markers of exerciseinduced muscle damage and inflammation obtained after a simulated trail running race. The recovery session was applied immediately after, 24h, 48h and 72h after subjects performed a 48min running treadmill exercise.…”
Section: Recovery From Exercise-induced Muscle Damagementioning
confidence: 99%
“…Esses resultados sugerem que o processo inflamatório no grupo tratado com crioterapia foi menor e estão de acordo com estudos prévios (26,32,76,77). A redução do infiltrado inflamatório e, consequentemente a prevenção do edema têm sido justificadas pelo mecanismo de vasocontrição induzida pela crioterapia (16,32,78).…”
Section: Sistema Antioxidanteunclassified
“…Esses resultados sugerem que o processo inflamatório no grupo tratado com crioterapia foi menor e estão de acordo com estudos prévios (26,32,76,77). A redução do infiltrado inflamatório e, consequentemente a prevenção do edema têm sido justificadas pelo mecanismo de vasocontrição induzida pela crioterapia (16,32,78). Contudo, encontramos estudos que sugerem que a crioterapia não altera o diâmetro arteriolar (26,79,80), mas aumenta o diâmetro venoso, possivelmente aumentando a reabsorção do edema (26,80).…”
Section: Sistema Antioxidanteunclassified
See 1 more Smart Citation